Cloning of CAT genes in Satsuma mandarin and their expression characteristics in response to environmental stress and arbuscular mycorrhizal fungi - Liu, Zhen; Cao, Ming-Ao; Kuča, Kamil; Alqahtani, Mashael Daghash; Muthuramalingam, Pandiyan; Wu, Qiang-Sheng (Plant cell reports, 2024)
CitCAT1 and CitCAT2 were cloned and highly expressed in mature leaves. High temperatures up-regulated CitCAT1 expression, while low temperatures and Diversispora versiformis up-regulated CitCAT2 expression, maintaining a low oxidative damage. Catalase (CAT), a tetrameric heme-containing enzyme, removes hydrogen peroxide (H2O2) to maintain low oxidative damage in plants exposed to environmental stress. This study aimed to clone CAT genes from Citrus sinensis cv. "Oita 4" and analyze their expression patterns in response to environmental stress, exogenous abscisic acid (ABA), and arbuscular mycorrhizal fungal inoculation. Two CAT genes, CitCAT1 (NCBI accession: PP067858) and CitCAT2 (NCBI accession: PP061394) were cloned, and the open reading frames of their proteins were 1479 bp and 1539 bp, respectively, each encoding 492 and 512 amino acids predicted to be localized in the peroxisome, with CitCAT1 being a stable hydrophilic protein and CitCAT2 being an unstable hydrophilic protein. The similarity of their amino acid sequences reached 83.24%, and the two genes were distantly related. Both genes were expressed in stems, leaves, flowers, and fruits, accompanied by the highest expression in mature leaves. In addition, CitCAT1 expression was mainly up-regulated by high temperatures (37 °C), exogenous ABA, and PEG stress within a short period of time, whereas CitCAT2 expression was up-regulated by exogenous ABA and low-temperature (4 °C) stress. Low temperatures (0 °C) for 12 h just up-regulated CitCAT2 expression in Diversispora versiformis-inoculated plants, and D. versiformis inoculation up-regulated CitCAT2 expression, along with lower hydrogen peroxide and malondialdehyde levels in mycorrhizal plants at low temperatures. It is concluded that CitCAT2 has an important role in resistance to low temperatures as well as mycorrhizal enhancement of host resistance to low temperatures.
Keywords: houby; Stress, Physiological; klonování DNA; Antioxidase; Mycorrhizae; mykorhiza; peroxid vodíku; Catalase; Citrus; fyziologický stres; Low temperatures; Hydrogen Peroxide; Fungi; Hydrogen peroxide; Cloning, Molecular; Mycorrhiza